THE INFLUENCE OF PRODUCT PRICE PERCEPTIONS AND PRODUK QUALITY ON PEOPLE’S PURCHASING DECISIONS IN ONLINE SHOPPING IN THE KELUANG SUB DISTRICT - Hendry Wijaya; Dadang Syaputra; Laidi Subardi; Febriyanti Febriyanti (Politeknik Negeri Media Kreatif, 2023)
This study aims to explain the influence of perceptions of product prices and product quality on people's purchasing decisions in shopping online for the people of Keluang District. The sample uses the Slovin formula. The data collection method used was to give questionnaires to the people of Keluang District, Musi Banyuasin Regency. Data were analyzed using the Quantitative Method, namely using the reliability test of the questionnaire, the classical assumption test, multiple regression analysis, correlation analysis, determination analysis, F test and T test with the help of SPSS 15.00 software for windows. The results of the study show that testing the hypothesis shows that partially there is a significant influence between the perception of product price (X1) and product quality (X2) on people's purchasing decisions in shopping online in the Keluang sub-district. Testing the effect of the independent variables together (simultaneously) on the dependent variable is carried out using the F test, stating that the hypothesis states that there is a simultaneous significant influence between the perception of product price (X1) and product quality (X2) on people's purchasing decisions in shop online in the Keluang sub-district community..